Hypophosphataemia following ferric derisomaltose and ferric carboxymaltose in patients with iron deficiency anaemia due to inflammatory bowel disease (PHOSPHARE-IBD): a randomised clinical trial. Issue 4 (9th September 2022) - Zoller, Heinz; Wolf, Myles; Blumenstein, Irina; Primas, Christian; Lindgren, Stefan; Thomsen, Lars L; Reinisch, Walter; Iqbal, Tariq
Abstract : Objective: Intravenous iron—a common treatment for anaemia and iron deficiency due to inflammatory bowel disease (IBD)—can cause hypophosphataemia. This trial compared the incidence of hypophosphataemia after treatment with ferric carboxymaltose (FCM) or ferric derisomaltose (FDI). Design: This randomised, double-blind, clinical trial was conducted at 20 outpatient hospital clinics in Europe (Austria, Denmark, Germany, Sweden, UK). Adults with IBD and iron deficiency anaemia (IDA) were randomised 1:1 to receive FCM or FDI at baseline and at Day 35 using identical haemoglobin- and weight-based dosing regimens. The primary outcome was the incidence of hypophosphataemia (serum phosphate <2.0 mg/dL) at any time from baseline to Day 35 in the safety analysis set (all patients who received ≥1 dose of study drug). Markers of mineral and bone homeostasis, and patient-reported fatigue scores, were measured. Results: A total of 156 patients were screened; 97 (49 FDI, 48 FCM) were included and treated. Incident hypophosphataemia occurred in 8.3% (4/48) FDI-treated patients and in 51.0% (25/49) FCM-treated patients (adjusted risk difference: −42.8% (95% CI –57.1% to –24.6%) p<0.0001). Both iron formulations corrected IDA. Patient-reported fatigue scores improved in both groups, but more slowly and to a lesser extent with FCM than FDI; slower improvement in fatigue was associated with greater decrease in phosphate concentration. Conclusion: Despite comparably effective treatment of IDA, FCM caused a significantly higher rate of hypophosphataemia than FDI. Further studies are needed to address the longer-term clinical consequences of hypophosphataemia and to investigate mechanisms underpinning the differential effects of FCM and FDI on patient-reported fatigue.